Six-coordinate ruthenium water oxidation catalysts bearing equatorial polypyridinedicarboxylato and axial phosphine ligands. (1st December 2022) - Yazdani, Sima; Breyer, Colton J.; Kumari, Pratibha; Rheingold, Arnold L.; Jazzar, Rodolphe; Bertrand, Guy; Grotjahn, Douglas B.
Graphical abstract: Ruthenium catalysts for water oxidation combining multidentate ONNO and ONNNO ligands and two phosphine ligands were made and characterized using NMR and UV-Vis spectroscopies, X-ray diffraction and electrochemistry, with the ONNNO complex showing reversible III-IV oxidation. The catalysts gave an initial burst of oxygen when driven with Ce IV, before stopping. Abstract: Ruthenium catalysts for water oxidation combining multidentate ligands [2, 2′:6′, 2″-terpyridine]-6, 6″-dicarboxylato (tda) and 2, 2′-bipyridine-6, 6′-dicarboxylato (bda) with apical phosphine ligands have been prepared. These new complexes were fully characterized by standard spectroscopic and single-crystal X-ray crystallography analyses, and their redox properties were evaluated by electrochemistry. Specifically, [Ru II (tda)(tris(2-furyl)phosphine)2 ] displayed two reversible redox waves that were assigned to the Ru II/III and Ru III/IV transitions, respectively. The number of turnovers in Ce IV -driven water oxidation reached 258 for the bda analog, and for the tda analog, early reaction rates were first order in initial catalyst concentration. The effects of adding fractional equivalents of Ce IV were studied using UV–vis spectroscopy. Steric and electronic changes in the axial phosphine ligand can exert their effects on the properties and catalytic activity of the resulting complexes, which may be useful when exploring other chemistry of these complexes.